ANALISIS KEBIJAKAN DESENTRALISASI SISTEM PENDIDIKAN NASIONAL DAN DAMPAKNYA TERHADAP PENDIDIKAN MADRASAH - Musfirah, Musfirah; Nurhadi , Nurhadi; Yuspiani , Yuspiani; Musdalifah , Musdalifah (Cendikia: Jurnal Pendidikan dan Pengajaran, 2025)
The education decentralization policy is part of the national education system reform that aims to provide broader authority to local governments in managing education. This study aims to critically analyze the impact of the decentralization policy on madrasah education in Indonesia. Using a descriptive qualitative approach and literature review, this study highlights the regulatory, structural, and implementation dynamics of the decentralization policy that have an impact on the governance, financing, and quality of madrasah education. The results of the study show that although decentralization opens up opportunities for innovation and increased local autonomy, madrasahs still face serious challenges related to limited access to resources, policy disparities between the central and regional governments, and lack of integration in the national education system. Therefore, policy reformulation and synergy between stakeholders are needed to ensure that madrasahs obtain an equal position within the framework of inclusive, equitable, and sustainable education development.